GDP as failed measure of the 21st century economic activity - Recher, Vedran (Oeconomica Jadertina, 2022)
This paper deals with GDP as the most widespread and most represented economic measure in the last seven decades. Although in the beginning GDP outlined what was important at the time, the paper shows that GDP hides more than it reveals in the modern economy. Despite numerous criticisms of economic growth and GDP as adequate measures for the 21st century, economies around the world in the midst of emerging from the crown of the crisis remain focused almost exclusively on that number. However, both the reports of the UN climate panel, and the very appearance of the corona virus have revealed all the shortcomings of such an approach. For example, the occurrence of natural disasters such as earthquakes and consequent reconstruction can significantly increase GDP, but this is not desirable from the aspect of the well-being of society. The paper outlines main critiques of growth and GDP and offers possible alternatives, some of which are already in use in neighboring countries.